Depiction of Pandemic in Indonesia Local Election 2020 Political Advertising - Robby Firmansyah; Dwi Marianto (IJCAS (International Journal of Creative and Arts Studies), 2021)
Abstract In the last quartal of 2020, during the Covid-19 pandemic, local elections were held in various cities and provinces in Indonesia. As a result of the public awareness of the pandemic situation and the urgent need for solutions to its implications, the Covid-19 pandemic became a suitable theme to be addressed on election campaign media. This paper aims to generate various patterns on how candidates utilized Covid-19 pandemic imageries in their political advertising to establish their personal brand. Thematic analysis was employed to identify the various patterns on how candidates utilized Covid-19 pandemic imageries in their political advertising. 329 Covid-19 related political advertisements from various candidates were reviewed to generate patterns on candidates’ personal brand establishment. The study found that promoting Covid-19 safety protocols, candidates' strategies, and appreciation toward frontline workers became three major themes in depicting the pandemic in Indonesia local elections 2020 political advertising. Covid-19 pandemic-related imageries are employed to perform their informative functions and as a context in which political advertising can perform its persuasive function.Penggambaran Pandemik pada Iklan Politik Pemilihan Kepala Daerah 2020 di Indonesia Abstrak Pada akhir tahun 2020, di tengah merebaknya pandemi Covid-19, dilakukan pemilihan kepala daerah di berbagai kota dan provinsi di Indonesia. Sebagai hasil dari kesadaran masyarakat terhadap situasi pandemi dan pentingnya solusi-solusi dalam menghadapi implikasinya, pandemi Covid-19 menjadi tema yang sesuai untuk dibahas pada media kampanye. Karya tulis ini ditujukan untuk membentuk tema-tema dari penggambaran pandemi Covid-19 yang digunakan oleh kandidat pemilihan pada iklan kampanye dalam membentuk citra dirinya. Analisis tematis digunakan untuk membentuk berbagai pola mengenai penggambaran pandemi Covid-19 yang digunakan oleh para kandidat pada iklan kampanyenya. 329 iklan kampanye terkait pandemi Covid-19 dari berbagai kandidat dikaji untuk menghasilkan pola-pola pembentukan citra diri kandidat pemilihan. Kajian ini membentuk tiga tema dari penggambaran pandemi pada iklan kampanye politik pemilihan kepala daerah 2020 yang berupa: mempromosikan protokol keamanan Covid-19, strategi kandidat, dan apresiasi terhadap pekerja garda depan Covid-19. Penggambaran terkait Covid-19 pada iklan kampanye tidak hanya digunakan untuk menjalankan fungsi informatif iklan kampanye, tetapi juga untuk menjalankan fungsi persuasifnya.